Experimental research of a rod glued along wood fibres - F. S. Shkoliar; A. G. Nikitin; A. I. Zatsepina (Vestnik MGSU)
Introduction. The objects of the research are experimental specimens of glued laminated wood with a steel rod glued along the wood fibres in each of them. The subject of the research is the values of resistance of wood to pulling out or push-through of the rod glued along the fibres, as well as the compliance of the joint. The goal of the research is to calculate the resistance according to the test results and compare the obtained value with normative data. The relevance of the research is due to the widespread application in construction of glued wood structures and joints on glued rods. The obtained data can be used in calculation models and in the calculation of nodes.Materials and methods. Experiment and calculation methods are used in the research.Results. The results of five specimens were used to obtain the values of total deformations for each stage of loading. It occurred due to chipping of the wooden element along the fibres at the border of the adhesive joint and the wood. Wood resistance and compliance values for each specimen were calculated and tabulated. The normative value of wood resistance was obtained. It exceeded the value specified in the normative document data. A numerical normative value of compliance was also obtained.Conclusions. The excess of the resistance obtained from the experiment over the value in the normative document indicates its applicability with provided safety factor. In the calculation of unique structures according to special technical specifications, it is possible to use an increased resistance value obtained as the result of the experiment. The compliance of a rigid joint on rods glued along the fibres is small. In wooden structures it is not possible to avoid it completely.